2020
DOI: 10.1016/j.ijid.2020.06.070
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric tuberculosis in the metropolitan area of Rio de Janeiro

Abstract: To evaluate the clinical characteristics, diagnostic approach, and treatment outcomes of tuberculosis (TB) in children living in a high-burden metropolitan area. Methods: This was a retrospective study, based on a medical chart review, involving children under 15 years old treated for TB between 2007 and 2016, in four primary health units (PHU) and three reference centers (RC) in five cities of Rio de Janeiro metropolitan area. Factors associated with TB treatment setting, microbiological diagnosis, and treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
2
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
4
2
0
4
Order By: Relevance
“…In the current study, Pleural effusion was the second most common EPTB (25.5%). This result was in line with the study findings reported from Athens, Greece (26.5%) ( 15 ) and Rio de Janeiro Brazil (27%)( 12 ). The above differences might be due to the different diagnostic skills of health professionals, laboratory diagnostic tools, and the child's clinical presentation.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In the current study, Pleural effusion was the second most common EPTB (25.5%). This result was in line with the study findings reported from Athens, Greece (26.5%) ( 15 ) and Rio de Janeiro Brazil (27%)( 12 ). The above differences might be due to the different diagnostic skills of health professionals, laboratory diagnostic tools, and the child's clinical presentation.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, those with HIV positive sero status were less likely to have a successful treatment outcome. This was similar to studies conducted in Addis Ababa, Ethiopia ( 9 ), Cote d'Ivore ( 31 ) Malawi ( 30 ), and the metropolitan area of Rio de Janeiro, Brazil ( 12 ). Those HIV positive individuals might have low immunity status, which can be co-infected with a number of pathogens with varying clinical manifestations.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations